Edukasi Disaster Preparedness Sebagai Upaya Peningkatan Public Awareness pada Anak Sekolah di SMK Negeri 9 Makassar - Mustari, Yery; Syahrul, Syahrul; Darwis, Andi Muflihah; Harisa, Akbar; Yodang, Yodang (Universitas Baiturrahim, 2024)
Indonesia is a country that often experiences natural disasters, one of which is flooding. Makassar City urban village level hazard assessment data shows that flooding is still the disaster with the largest potential area in Makassar City. Preparedness is a preparation or planning about preventive actions against disaster events and possible disaster events. This community service activity is carried out as an effort to prevent damage and losses caused by floods in flood-prone areas. The purpose of this community service is to increase the knowledge of students of SMK Negeri 9 Makassar in handling flood disasters through disaster preparedness education. The educational methods provided are counseling, discussion, and demonstration/roleplay. Of the 35 participants, as many as (54.4%) had sufficient knowledge and increased to (51.4%) had good knowledge after being given education. It is hoped that this activity will become a reference for students and all school staff in dealing with floods, and can form a special student organization that teaches training on flood disaster preparedness.